Vitamin D regulates ion regulation by affecting the ionocyte differentiation in zebrafish (Danio rerio) larvae - Lin, Chia-Hao; Chang, Hung-Chi; Liu, Sian-Tai; Hu, Huei-Jyun (Frontiers in Marine Science, 2023)
Freshwater teleosts frequently face the stress of varied ion and pH levels; therefore, they have developed related defense mechanisms to maintain the homeostasis of body-fluid ion and acid-base balance. The different subtypes of ionocytes expressed in the branchial epithelium of adult fish or the skin of larvae are the major sites for fish ion regulation. 1α,25-dihydroxyvitamin D3 (1α,25(OH)2D3), the bioactive form of vitamin D, is a steroid hormone that is involved in the regulation of Ca2+ uptake and acid secretion in teleosts. Our results revealed that 1α,25(OH)2D3 levels were not changed in zebrafish larvae upon exposure to low Na+ freshwater compared to normal freshwater. In contrast, 1α,25(OH)2D3 levels were substantially higher in fish exposed to acidic and low Ca2+ freshwater than in those exposed to normal freshwater. Some hormones regulate ion regulation and acid secretion by modulating ionocyte differentiation and/or proliferation in teleosts; however, the role of vitamin D in this process is unclear. Zebrafish larvae were used as a model in the present study to explore the effect of vitamin D on ionocyte proliferation and/or differentiation. The present study indicated that 1α,25(OH)2D3 treatment increased the number of foxi3a-positive cells, ionocyte progenitors, and mature ionocytes. However, the number of P63-positive cells and epidermal stem cells did not change in the zebrafish larvae treated with 1α,25(OH)2D3. These results revealed that vitamin D exerts a positive effect on the number of ionocytes by increasing the differentiation of ionocytes. Increased ionocyte differentiation by vitamin D is suggested to elevate the capacity of ion regulation and acid secretion in zebrafish to cope with external stress. The present findings indicate the role of vitamin D in the regulation of ionocyte differentiation and provide new insights into the mechanisms of stress adaptation of fish.